POST-DISCHARGE LEARNING NEEDS OF PATIENTS WHO HAD UNDERGONE CORONARY ARTERY BYPASS GRAFTING SURGERY - Uzun, Özge; Demirkıran, Gülsen (Ege Üniversitesi, 2012)
Aim: Aim of this study was to determine post discharge learning needs of patients who had undergone coronary artery bypass grafting surgery CABG for the first time, and whether these needs change according to the patients’ some identifier characteristics. Methods: This descriptive study was conducted on patients in Cardio Vascular Surgery Clinic of a university hospital. The sample of this study consisted of 80 patients. Data were collected using by the Patient Information Form and Patient Learning Needs Scale PLNS . In statistical analyze of data was used means, frequencies, Kruskall Wallis H, Mann-Whitney U, Student-t tests. Results: The mean total score learning needs of patients was 183.48±23.36, with an importance level of 3.66 were found to be very important level. The most important learning need of patients was the life activities 37.60±4.93, importance level: 4.93 and the least important learning need was the emotions related to the situations 12.66±4.04, importance level: 2.53 . It was found that PLNS total scale mean scores of female patients, housewives, patients who had not received discharging education, and patients who had only received the discharging education from the doctor were higher than other patients, and differences between mean scores of groups were statistically significant p

Amaç: Bu araştırmanın amacı, ilk kez koroner arter bypass greft KABG ameliyatı geçiren hastaların taburculuk sonrası öğrenim gereksinimlerini ve bu öğrenim gereksinimlerinin hastaların bazı tanıtıcı özelliklerine göre farklılık gösterip göstermediğini belirlemekti. Yöntem: Tanımlayıcı türden olan bu çalışma bir üniversite hastanesinin Kalp Damar Cerrahisi kliniğindeki hastalar üzerinde yürütüldü. Çalışmanın örneklemini 80 hasta oluşturdu. Veriler Hasta Bilgi Formu ve Hasta Öğrenim Gereksinimleri Ölçeği HÖGÖ kullanılarak toplandı. Verilerin istatistiksel analizlerinde ortalamalar, sıklıklar, Kruskal Wallis H, Mann Whitney U ve Student’s t testleri kullanıldı. Bulgular: Hastaların öğrenim gereksinimleri toplam puan ortalamasının 183.48±23.36 ile çok önemli düzeyde önemlilik düzeyi: 3.66 olduğu bulundu. Hastalar için en önemli öğrenim gereksinimi yaşam aktiviteleri alt boyutu 37.60±4.93, önemlilik düzeyi: 4.93 , en az önemli öğrenim gereksinimi ise duruma ilişkin duygular alt boyutuna 12.66±4.04, önemlilik düzeyi: 2.53 ilişkindi. Kadın hastaların, ev hanımlarının, taburculuk eğitimi almayan hastaların, sadece hekimden taburculuk eğitimi alan hastaların HÖGÖ toplam puan ortalamaları diğer hastalarınkinden daha yüksek ve grupların puanları arasındaki fark istatistiksel olarak anlamlı bulundu p
KORONER ARTER BYPASS GREFT AMELİYATI GEÇİREN HASTALARIN TABURCULUK SONRASI ÖĞRENİM GEREKSİNİMLERİ